Let battle commence. (Economist, 2002)
In February 2002, Microsoft launched a set of tools to develop web services and a software framework to run them, taking the battle to decide who will provide the dominant software platform of the next generation of computing a stage further. Microsoft, which has ended up being the platform of choice for web-based applications and is now moving toward supporting web services, has produced its .NET plan, created to leapfrog it back into the lead in the market. An array of competitors, which includes IBM, Oracle, and Sun, is touting a technology based on the Java programming language, officially called Java 2 Platform Enterprise Edition. It is the Internet, which has allowed computing to become increasingly distributed, that is driving the rivalry over who will dominate the world of web services. Details of how both .NET and Java 2 will operate are provided.